Environmental and Geographic Conditions on the Breeding Grounds Drive Bergmannian Clines in Nightjars - Skinner, Aaron A.; Korpach, Alicia M.; Åkesson, Susanne ; 0000-0001-9039-2180; Bakermans, Marja H.; Bayne, Erin M.; Benson, Thomas J.; Boano, Giovanni; Brigham, R. Mark; Christiansen, Simon S.; Conway, Greg J.; Davy, Christina M.; Evens, Ruben; et al. (Journal of Biogeography, 2025)
Aim: To evaluate (1) whether three migratory nightjar species (Family Caprimulgidae) adhere to Bergmann's rule, (2) whether environmental factors on the breeding or wintering grounds determine body size, and (3) which mechanistic hypotheses best explain Bergmannian patterns in body size. Location: North and South America; Europe and Africa. Taxon: Eastern whip-poor-will (Antrostomus vociferus), Common nighthawk (Chordeiles minor) and European nightjar (Caprimulgus europaeus). Methods: We used GPS tracking and morphometric data to assess competing hypotheses explaining variation in body size for each species, based on their breeding (n = 3388) and wintering (n = 189) locations. Results: All three species exhibited Bergmannian patterns in body size, providing the first evidence that nightjars conform to Bergmann's rule despite adaptations to severe environmental conditions. Environmental and geographic variables at breeding sites were stronger predictors of body size than wintering-site variables. Although we found partial support for Bergmann's temperature regulation hypothesis, geographic variables, rather than specific environmental factors, emerged as the strongest predictors of body size variation. Main Conclusions: Latitude and longitude correlated strongly with environmental variables and migratory distance; thus, these geographical variables likely encompass many factors that influence body size in nightjars. The present study is among the first to use tracking data from individual birds to understand how environmental pressures across the annual cycle are related to body size. Our findings highlight the critical role of geographic breeding-ground factors in shaping Bergmannian patterns, offering robust evidence to support nearly two centuries of research since Bergmann's rule was first described in 1847.
Publisher Copyright: © 2025 The Author(s). Journal of Biogeography published by John Wiley & Sons Ltd.
Keywords: annual cycle; Bergmann's rule; body size; Caprimulgidae; GPS tracking; mechanism; nightjars; productivity; seasonality; temperature regulation